2014
DOI: 10.1542/peds.2013-1760
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Pulse Oximetry in Children

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Saturations from pulse oximetry (SpO 2 ) may overestimate arterial oxygen saturations measured by CO-oximetry (SaO 2 ). The overestimation can be affected by location of measurement, perfusion, and skin color. Previous studies are limited by small numbers of observations in a hypoxemic range. WHAT THIS STUDY ADDS:This large sample of hypoxemic patients identified that SpO 2 typically overestimates SaO 2 . Bias and precision varied throughout the SpO 2 range. The SpO 2 range of 81%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
107
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(121 citation statements)
references
References 13 publications
9
107
0
5
Order By: Relevance
“…Accuracy of pulse oximetry is poor, especially in the 76% to 90% range. 110 Further, it has been well demonstrated that oxygen saturation has much less impact on respiratory drive than carbon dioxide concentrations in the blood. 111 There is very poor correlation between respiratory distress and oxygen saturations among infants with lower respiratory tract infections.…”
Section: Action Statement Profile Kas 6bmentioning
confidence: 99%
“…Accuracy of pulse oximetry is poor, especially in the 76% to 90% range. 110 Further, it has been well demonstrated that oxygen saturation has much less impact on respiratory drive than carbon dioxide concentrations in the blood. 111 There is very poor correlation between respiratory distress and oxygen saturations among infants with lower respiratory tract infections.…”
Section: Action Statement Profile Kas 6bmentioning
confidence: 99%
“…For example, pulse oximetry in a low range (Ͻ 87%) may have 95% prediction intervals greater than Ϯ 10% against co-oximetry. 20 For example, if the pulse oximeter reading is 85%, then 50% of the time, the actual S aO 2 on co-oximetry would lie between 75 and 83%, but for 95% certainty, the S aO 2 could range from 64 to 89%. Nevertheless, pulse oximetry in a low range is routinely used for clinical decision making for children with cyanotic congenital heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…16 Oxygen desaturation was defined as a SpO 2 \ 92% for normoxic patients or as C 5% below awake admission values for cyanotic patients. 17,18 Following completion of the echocardiographic exam, patients were evaluated and discharged according to previously published discharge criteria for pentobarbital sedation in our institution.…”
Section: Résumémentioning
confidence: 99%